Disparitas Pendapatan di Jawa Tengah - Muliasari Pinilih (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
The income disparity is still a concern for the Central Java regional government. Several factors can cause inequality of income. Therefore, this study aims to analyze the effect of economic growth, an investment that will be divided into PMDN (Domestic Investment) and PMA (Foreign Investment), inflation, labor force, population growth, and sector contribution to income inequality in Central Java in the 2014-2098 period. The data to be analyzed is obtained from the Central Java Province BPS and analyzed using regression analysis, t-test, and F-test. The results obtained indicate that only PMDN (Domestic Investment) and sector contributions partially influence income disparity. Simultaneously, economic growth, PMA (Foreign Investment), inflation, labor force, and population growth are recorded as not being able to affect a difference in income distribution partially.